‘I am Death, I have the bow ready’: Iconographical Analysis of the Paintings of Santa María de Mosteiro Church, Interpretation Proposal - Lázaro Romero, Irene (Eikón / Imago, 2021)
Santa María de Mosteiro church’s mural paintings have an unusual iconographical programme that hasn’t been studied in depth. It includes a depiction of Death in relation to a jousting scene, which makes the iconography unparalleled both in the Iberian Peninsula and in European art in general. The aim of this paper is to approach the paintings of the galician church and propose an interpretation of the iconographic programme of the paintings.